Feasibility of using dialysis for determining calcium ion concentration and pH in calcium-fortified soymilk at high temperature - Pathomrungsiyounggul P. (2014)
Dialysis was performed to examine some of the properties of the soluble phase of calcium (Ca) fortified soymilk at high temperatures. Dialysates were obtained while heating soymilk at temperatures of 80 and 100 °C for 1 h and 121 °C for 15 min. It was found that the pH, total Ca, and ionic Ca of dialysates obtained at high temperature were all lower than in their corresponding nonheated Ca-fortified soymilk. Increasing temperature from 80 to 100 °C hardly affected Ca ion concentration ([Ca(2+)]) of dialysate obtained from Ca chloride-fortified soymilk, but it increased [Ca(2+)] in dialysates of Ca gluconate-fortified soymilk and Ca lactate-fortified soymilk fortified with 5 to 6 mM Ca. Dialysates obtained at 100 °C had lower pH than dialysate prepared at 80 °C. Higher Ca additions to soymilk caused a significant (P≤ 0.05) reduction in pH and an increase in [Ca(2+)] of these dialysates. When soymilk was dialyzed at 121 °C, pH, total Ca, and ionic Ca were further reduced. Freezing point depression (FPD) of dialysates increased as temperature increased but were lower than corresponding soymilk samples. This approach provides a means of estimating pH and ionic Ca in soymilks at high temperatures, in order to better understand their combined role on soymilk coagulation.